2017
DOI: 10.1097/nmd.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Affiliate Stigma Between Family Caregivers of People With Different Severe Mental Illness in Taiwan

Abstract: The family caregivers of people with mental illness may internalize the public stereotypes into the affiliate stigma (i.e., the self-stigma of family members). This study aimed to compare the affiliate stigma across schizophrenia, bipolar disorder, and major depressive disorder, and to investigate potential factors associated with affiliate stigma. Each caregiver of family members with schizophrenia (n = 215), bipolar disorder (n = 85), and major depressive disorder (n = 159) completed the Affiliate Stigma Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 51 publications
4
67
1
2
Order By: Relevance
“…Table presents the characteristics of the eligible studies. All these studies were published between 1994 and 2017 and conducted in the United States (Bassirnia et al., ; Biegel, Milligan, Putnam, & Song, ; Greenberg, Kim, & Greenley, ), Hong Kong (Chen et al., ; Mak & Cheung, , ), Taiwan (Chang, Yen, Jang, Su, & Lin, ; Chang et al., ; Wu & Chen, ), UK (Kingston, Onwumere, Keen, Ruffell, & Kuipers, ; Whitney, Haigh, Weinman, & Treasure, ), India (Koschorke, Thornicroft, Thara, Balaji, & Patel, ; Singh, Mattoo, & Grover, ), Israel (Hasson‐Ohayon, Levy, Kravetz, Vollanski‐Narkis, & Roe, ), Sri Lanka (Fernando, Deane, & McLeod, ; Fernando, Deane, McLeod, et al., ), Ethiopia (Girma et al., ; Weldeslasie Hailemariam, ), Turkey and Brazil (Ferreira de Araujo Jorge & Chaves, ), Portugal (Gonçalves‐Pereira et al., ), and Japan and Korea (Hanzawa et al., , ). All studies were cross‐sectional, except for one follow‐up study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table presents the characteristics of the eligible studies. All these studies were published between 1994 and 2017 and conducted in the United States (Bassirnia et al., ; Biegel, Milligan, Putnam, & Song, ; Greenberg, Kim, & Greenley, ), Hong Kong (Chen et al., ; Mak & Cheung, , ), Taiwan (Chang, Yen, Jang, Su, & Lin, ; Chang et al., ; Wu & Chen, ), UK (Kingston, Onwumere, Keen, Ruffell, & Kuipers, ; Whitney, Haigh, Weinman, & Treasure, ), India (Koschorke, Thornicroft, Thara, Balaji, & Patel, ; Singh, Mattoo, & Grover, ), Israel (Hasson‐Ohayon, Levy, Kravetz, Vollanski‐Narkis, & Roe, ), Sri Lanka (Fernando, Deane, & McLeod, ; Fernando, Deane, McLeod, et al., ), Ethiopia (Girma et al., ; Weldeslasie Hailemariam, ), Turkey and Brazil (Ferreira de Araujo Jorge & Chaves, ), Portugal (Gonçalves‐Pereira et al., ), and Japan and Korea (Hanzawa et al., , ). All studies were cross‐sectional, except for one follow‐up study.…”
Section: Resultsmentioning
confidence: 99%
“…Another study indicated that a high level of caregiver self‐stigma was independently associated with the highest education level in the household being secondary school level (9th to 12th Standard) (Koschorke et al., ). Two cross‐sectional studies reported that young age was associated with high level of affiliate stigma (Koschorke et al., ; Singh et al., ), whereas another study found no relationship between age and affiliate stigma (Chang et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health-related stigma are associated with various conditions, such as mental illnesses (Chang, Wu, Chen, & Lin, 2016;Chang, Yen, Jang, Su, & Lin, 2017;Corrigan, 2000), infectious diseases (Mak et al, 2006;Zhang, Liu, Bromley, & Tang, 2007), sexual orientations (Herek, 2007), race, and obesity (Dean, Roth, & Bobko, 2008;Lin & Lee, 2017;Roehling, Roehling, & Pichler, 2007). Manifestations of stigma vary in the context of diverse health conditions and cultures (Parker & Aggleton, 2003).…”
Section: Introductionmentioning
confidence: 99%